Juridical analysis of notaries' role in drafting and ratifying deeds of amendment to limited liability companies' articles of association for shareholders' legal certainty - Dahliana Munthe; H.M. Soerya Respationo; Erniyanti Erniyanti (Annals of Justice and Humanity, 2025)
Purpose: This study aims to analyze the legal framework regulating the role of notaries in drafting and ratifying deeds of amendment to the Articles of Association of a Limited Liability Company (PT), to examine the implementation of this role from the perspective of legal certainty for shareholders, and to identify obstacles along with their legal solutions. Methodology: This study applies normative and empirical juridical methods through a statute and socio-legal approach. Data were gathered from literature and field research, including interviews with notaries and stakeholders, and qualitatively analyzed using theories of positive law, legal system, and legal certainty. Results: The findings indicate that the notary’s role in amendments to articles of association is legally regulated under UUJN, UUPT, and related implementing regulations. However, practical challenges remain, such as nonconformity of deeds with regulations, technical barriers in the SABH system, and insufficient transparency and participation of shareholders. Conclusion: Although the regulatory framework governing notarial authority is comprehensive, its implementation still encounters juridical, administrative, and substantive obstacles. This undermines the assurance of legal certainty for shareholders and highlights the need for reform in practice. Limitation: The study is limited by its reliance on qualitative interviews with selected notaries and stakeholders in specific regions, which may not fully represent diverse practices nationwide. Contribution: This research contributes to the development of corporate law by providing insights into harmonizing regulations, strengthening notarial capacity through training and legal technology, and promoting shareholder legal literacy to enhance legal certainty and minimize disputes.